Cell-free translation of avian erythroblastosis virus RNA. - Pawson, T (1980)
Avian erythroblastosis virus (AEV) RNA rescued from nonproducer cells by superinfection with a helper virus is translated into three polypeptides in the messenger-dependent rabbit reticulocyte lysate. A 75,000 molecular weight polypeptide (P75AEV) is synthesized from 28S RNA and is encoded by the 5' section of the AEV RNA, including gag-related and AEV-specific sequences. The P75AEV synthesized in infected cells and the P75AEV synthesized in the cell-free system are electrophoretically identical. A 44,000 molecular weight polypeptide (P44AEV) is synthesized from 20-24S RNA, apparently from the 3' section of the AEV-specific RNA sequence. A minor 37,000 molecular weight polypeptide (P37AEV) is synthesized from 20S AEV RNA. A comparison is drawn between the cell-free products of MC29 and AEV RNAs.